Projectile for a New Intermediate Cartridge - Krzysztof PIASTA; Przemysław KUPIDURA; Grzegorz LEŚNIK (Problemy Mechatroniki)
Evolution of contemporary military conflicts has revealed some shortcomings of existing individual small arms ammunition. The first attempts to undertake research and development works on new weapons and ammunition were made in the USA, however, some projects are also being launched in other countries. This paper presents a short review of the newly developed rounds for perspective small arms systems as well as an attempt to determine a caliber of perspective individual weapon. For this purpose, some preliminary external and terminal ballistic analyses were conducted for various diameter projectiles of the same design.